Serological prevalence of Leptospira spp. in horses in Ukraine - Ukhovskyi, V. V.; Korniienko, L. Y.; Chechet, O. M.; Aliekseieva, G. B.; Polishchuk, O. D.; Mietolapova, H. M.; Tsarenko, T. M.; Romanko, M. Y.; Pyskun, O. O. (Regulatory Mechanisms in Biosystems, 2023)
Leptospirosis, a zoonotic disease with constantly evolving pathogens, poses risks to both human and animal health. We investigated the prevalence of Leptospira spp. among horses in Ukraine from 2007 to 2021, encompassing clinical and subclinical cases. The study utilized data from the State Research Institute for Laboratory Diagnostics and Veterinary and Sanitary Expertise (2007–2021) to analyze leptospirosis prevalence in Ukrainian horses. Seroprevalence was calculated for each region. Equine leptospirosis outbreaks were retrospectively analyzed based on serological data from microagglutination reaction (MRA) studies using eight major serogroups. A geospatial analysis, utilizing quantile classification with five data classes, was conducted. Spanning 2007–2021, our analysis evaluated the prevalence and dynamics of equine leptospirosis in Ukraine. Serum samples tested for Leptospira antibodies exhibited varying dynamics over this period, with the highest and lowest rates observed in different years. Among the 125,101 horse serum samples analyzed, 10.8% tested positive for leptospirosis. The incidence rate fluctuated, peaking in certain years. The dominant serovars were Copenhageni (32.8%), Bratislava (16.1%), Grippotyphosa (15.4%), and Canicola (13.2%), while mixed reactions constituted 55.1% of positive cases. The analysis also revealed shifts in the prevalence of specific serovars over time. Geospatial analysis showcased the distribution of positive cases for each serovar across Ukraine’s regions. The highest infection rates were observed in the eastern and northern regions, each characterized by distinct serovar prevalence. The etiologic composition map depicted varying serovar proportions among different regions. Furthermore, the density map delineated regions with different risk levels, with several regions falling into the "very high risk" category, while others like Odesa and Lviv were classified as low risk due to fewer positive leptospirosis cases. Detection of specific serovars like Tarassovi, Pomona, and Canicola in horses points to potential pathogen sources such as cattle, pigs, and dogs. The dominance of serovar Copenhageni (serogroup Icterohaemorrhagiae), accounting for 32.8% of seropositivity, reflects close contact with rodents, recognized reservoirs of this serogroup. These findings illuminate the evolving prevalence and distribution of leptospirosis in Ukrainian horses, offering vital insights for targeted interventions and disease management strategies. The insights garnered from this study can hold significant value for equine veterinarians, aiding the development of tailored preventive and control measures adapted to specific regions with varying risk levels. Our research offers a comprehensive examination of equine leptospirosis from both ecological and geographical perspectives, unveiling pivotal observations.